Armored BCMA CAR T Cells Eliminate Multiple Myeloma and Are Resistant to the Suppressive Effects of TGF-β - Alabanza, Leah M.; Xiong, Ying; Vu, Bang; Webster, Brian; Wu, Darong; Hu, Peirong; Zhu, Zhongyu; Dropulic, Boro; Dash, Pradyot; Schneider, Dina (Frontiers in Immunology, 2022)
CAR T-cell therapies targeting the B-cell maturation antigen eliminate tumors in relapsed/refractory multiple myeloma patients, however durable remissions remain difficult to attain. Transforming growth factor beta (TGF-β) is a multifunctional cytokine abundantly expressed in the multiple myeloma bone marrow niche, where it promotes an immunosuppressive tumor microenvironment. We hypothesized that BCMA CAR T-cells armored to resist the suppressive effects of TGF-β will provide an advantage in treating multiple myeloma. The armored B2ARM CAR T cells, co-expressing BCMA targeting CAR with TGF-β dominant-negative receptor II, were generated by lentiviral transduction of primary human CD4+ and CD8+ T cells. The B2ARM CAR T cells eliminated MM.1S multiple myeloma targets in long-term cytotoxicity assays, even under TGF-β-high conditions, whereas cytotoxic function of the non-armored B2 CAR -T cells was inhibited by TGF-β. Concordantly, after long-term exposure to targets in the presence of TGF-β, the B2ARM CAR T cells were enriched for Granzyme B, CD107a, Ki67 and polyfunctional cells T-cells (double or triple-positive for IFN-γ, IL-2 and/or TNF-α), as determined by flow cytometry. In addition, the B2ARM CAR T-cells, but not the conventional B2 CAR T-cells, resisted the TGF-β-mediated suppression of activation (CD25), exhaustion (PD-1, LAG3), and differentiation to T effectors (CD45RA+ CD45RO-CD62L-). In NSG mice bearing RPMI-8226 tumors overexpressing TGF-β, the B2ARM CAR mediated 100% tumor rejection and survival, superior infiltration of tumors on day 7 post CAR T treatment (%CD3+CAR+), and greater expression of IFN-γ, TNF-α, Ki67, Granzyme B, and PD-1, as compared to tumor-infiltrating non-armored B2 CAR T-cells. In NSG RPMI-8226 xenograft model in which tumors were additionally supplemented with TGF-β injections on days -1 through 11 of CAR T treatment, the B2ARM CAR T cells rejected tumors faster than the non-armored B2 CARs, and showed greater numbers of CD3+ and CD3+CAR+, central memory (CD45RO+CD62L+) and effector memory (CD45RO+CD62L-) T cells in the peripheral blood 18 days after treatment. In summary, the armored B2ARM CAR T cells mediate superior persistence, proliferation, multi-functionality, effector differentiation and anti-tumor function in pre-clinical models of multiple myeloma, while abrogating TGF-β-mediated suppression.